Dinamika Psikologis Wanita Yang Mengalami Konflik Peran Ganda - Dena Wijaya, Putri Ade; Abdillah, Rijal (Universitas Pahlawan Tuanku Tambusai, 2024)
Women experience conflict both at work and in their personal lives. This can lead to some role conflicts. Whether or not a career woman should perform her roles as a worker and a housewife In other words, women are more likely to experience a double-role conflict than men. Referring to such phenomena, the study aims to explore in depth how women’s lives are experiencing double-role conflicts. The method used in this research is qualitative with a phenomenological approach. The study involved two subjects and two informants. Two subjects of this study were a housewife and a career woman working at one of the private hospitals and private companies in Bekasi City. The data collection method uses in-depth interviews, participant observations, and documentation. This research is expected to be able to reveal events or events experienced by both subjects related to the life conflict of dual roles. Based on the results of the research, it was found that the life conflict of double roles has demands that are not easily solved given her roles as a housewife and a career woman. Both subjects experience Family Interference with Work (FIW) dan Work Interference with Family (WIF). The study recommends that women who experience double-role conflict should be able to establish good communication with their husbands as well as interrelationships with other people relating to large families, such as parents, parents, and parents. In addition, women in conflict should also be able to implement a good coping strategy.